2024
DOI: 10.1038/s41467-024-45646-9
|View full text |Cite
|
Sign up to set email alerts
|

A transient protein folding response targets aggregation in the early phase of TDP-43-mediated neurodegeneration

Rebecca San Gil,
Dana Pascovici,
Juliana Venturato
et al.

Abstract: Understanding the mechanisms that drive TDP-43 pathology is integral to combating amyotrophic lateral sclerosis (ALS), frontotemporal lobar degeneration (FTLD) and other neurodegenerative diseases. Here we generated a longitudinal quantitative proteomic map of the cortex from the cytoplasmic TDP-43 rNLS8 mouse model of ALS and FTLD, and developed a complementary open-access webtool, TDP-map (https://shiny.rcc.uq.edu.au/TDP-map/). We identified distinct protein subsets enriched for diverse biological pathways w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 112 publications
0
3
0
Order By: Relevance
“…Formaldehyde crosslinking and homogenization of brain tissue was adapted from previous protocols (Liu-Yesucevitz et al, 2010; San Gil et al, 2024; Sap et al, 2021). 500 µl of 0.5% formaldehyde in PBS was added to 30 mg of frozen mouse brain tissue, previously crushed under N 2 and placed on a rotating wheel for 10 mins at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Formaldehyde crosslinking and homogenization of brain tissue was adapted from previous protocols (Liu-Yesucevitz et al, 2010; San Gil et al, 2024; Sap et al, 2021). 500 µl of 0.5% formaldehyde in PBS was added to 30 mg of frozen mouse brain tissue, previously crushed under N 2 and placed on a rotating wheel for 10 mins at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…These studies identified multiple disease-related changes in biological pathways. However, these analyses were performed using soluble protein fractions (Lee et al, 2023; San Gil et al, 2024) without TDP-43 immunoprecipitation, and would therefore not accurately capture the TDP-43-associated SG proteome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation